﻿Un portrait de David par Nicolas-Bernard Lépicié? - Bédard, Sylvain (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1994)
In this article, the author proposes that the physiognomy of the painter Jacques-Louis David should be recognized in a Portrait d’homme belonging to the Musée Bonnat in Bayonne. This comparison is first of all based on the fairly close resemblance that exists between this head, painted by Nicolas-Bernard Lépicié (1735-84), and reliable, known effigies of David, such as his self-portrait of 1794 in the Louvre. It must be said that the quite particular characteristics of the painter have always facilitated his identification. David, in fact, had the left part of his face deformed by a swelling, the outcome of a wound received during his youth. This physical characteristic is present in Lépicié's sitter, along with other distinctive traits of the painter, such as his broad, straight brow, his circumflex-shaped eyebrows, and finally, the slightly bulging tip of his nose.We know, moreover, that the two painters each occupied a studio in the Louvre between the years 1782 and 1784. It may be that this “neighbourhood” provided the occasion for them to cultivate a certain relationship and ties of which the Bayonne canvas now constitutes the only evidence.